Burden of vaccine-preventable diseases among at-risk adult populations in the US - Irina Kolobova; Mawuli Kwame Nyaku; Anna Karakusevic; Daisy Bridge; Iain Fotheringham; Megan O'Brien (Taylor & Francis Group, 2022)
Life-course immunization holds significant benefit for population health by reducing the burden of vaccine-preventable diseases (VPD) through vaccinating individuals at different stages and circumstances in life. The study aimed to determine the epidemiologic, clinical, economic, and societal burden of VPDs among at-risk adult subpopulations in the United States. A systematic literature review was conducted for articles published between January 2010 and June 2020, which identified 72 publications. There was heterogeneity in available epidemiology data, with the prevalence of VPDs ranging from 1.1% to 68.7%. Where the disease burden was described, outcomes were typically worse among high-risk subpopulations than in the general population. Several VPDs, including herpes zoster, meningococcal, and pneumococcal infections were associated with increased costs. This review suggests that subpopulations may not frequently interact with the healthcare system, or their risk factors may not be recognized by healthcare providers, and therefore individuals may not be appropriately targeted for vaccination.